La responsabilidad social del estado frente a la rehabilitación de adolescentes infractores en el Ecuador - Armijos Taisha, Jaime Vinicio (2010)
The increase of the juvenile delinquency in recent years, has motivated that develop the current investigation, focusing the social responsibility of the State in front of the rehabilitation of smaller offenders in Ecuador which is why have carried out a study and thorough analysis of principles mentioned in the Convention of the Boy's Rights, rights and guarantees of the children, girls and adolescents considered in Constitution of the Republic of Ecuador and the legal regulation of the current Code of the Niñez and the Adolescence, instrument that the application of member measures regulates educational for smaller offenders, for cases of freedom hardship of the minors considered by Rules of Beijing and the Convention of the Boy's Rights, as a last resort, Our Minors Code foresees the operation of the centers of internment and the responsibility of the State when it comes to the tracking and control of the measures educational member within internment centers for teenage offenders. During the development of the work investigative proved the use of all existing norms within the legislation of minors. Within the conceptual framework the literature checkup was made concerning rights and guarantees of the children, girls and adolescents in Ecuador, in of the doctrinaire study a history is done of the evolution of the children' rights, the economic member situation of the minors offenders in the country; as well as an analysis is done on educational member measures and the responsibility of the State. Thanks to the fulfilled Field research conclude the current work proving the lack of support on the part of the State to the Center of Minors Internment, without which you can not give a real rehabilitation and reintegration of the minors offenders that are returned again to the society, for which at the end of our work focus several recommendations and a reform proposal to the Code of the Children’s and the Adolescence with which expect great resources is warranted for the adaptation and implementation of the Centers of Internment of the country which consequently better deal would be given, protection and rehabilitation of the minors offenders.